Pneumothorax associated with nontuberculous mycobacteria: A retrospective study of 69 patients. Issue 29 (July 2016) - Ueyama, M; Asakura, Takanori; Morimoto, Kozo; Namkoong, Ho; Matsuda, Shuichi; Osawa, Takeshi; Ishii, Makoto; Hasegawa, Naoki; Kurashima, Atsuyuki; Goto, Hajime
Abstract : Abstract: The incidence of nontuberculous mycobacterial pulmonary disease (NTMPD) is increasing worldwide. Secondary spontaneous pneumothorax occurs as a complication of underlying lung disease and is associated with higher morbidity, mortality, and recurrence than primary spontaneous pneumothorax. We here investigated the clinical features and long-term outcomes of pneumothorax associated with NTMPD. We conducted a retrospective study on consecutive adult patients with pneumothorax associated with NTMPD at Fukujuji Hospital and Keio University Hospital from January 1992 to December 2013. We reviewed the medical records of 69 such patients to obtain clinical characteristics, radiological findings, and long-term outcomes, including pneumothorax recurrence and mortality. The median age of the patients was 68 years; 34 patients were women. The median body mass index was 16.8 kg/m 2 . Underlying pulmonary diseases mainly included chronic obstructive pulmonary disease and pulmonary tuberculosis. On computed tomography, nodules and bronchiectasis were observed in 46 (98%) and 45 (96%) patients, respectively. Consolidation, pleural thickening, interlobular septal thickening, and cavities were most common, and observed in 40 (85%), 40 (85%), 37 (79%), and 36 (77%) patients, respectively. Regarding pneumothorax treatment outcomes, complete and incomplete lung expansion were observed in 49 patients (71%) and 15 patients (22%), respectively. The survival rate after pneumothorax was 48% at 5 years. By the end of the follow-up, 33 patients had died, and the median survival was 4.4 years with a median follow-up period of 1.7 years. The rate of absence of recurrence after the first pneumothorax was 59% at 3 years. By the end of the follow-up, 18 patients had experienced pneumothorax recurrence. Furthermore, 12/18 patients (66%) with recurrent pneumothorax died during the study period. Twenty-three patients (70%) died because of NTMPD progression. Low body mass index (BMI) was a negative prognostic factor for pneumothorax associated with NTMPD in multivariate analysis (HR 0.79, 95% CI 0.64−0.96; P = 0.018) Patients with pneumothorax associated with NTMPD have advanced disease, a high rate of pneumothorax recurrence, and poor prognosis, regardless of the pneumothorax treatment used. Further improvements in early diagnosis of NTMPD and appropriate management in both NTMPD and NTMPD-associated pneumothorax are needed.